Epilepsy in the tropics: Emerging etiologies. (January 2017) - Carrizosa Moog, Jaime; Kakooza – Mwesige, Angelina; Tan, Chong Tin
Abstract: Epilepsy is considered by the World Health Organization a public health priority with more than 50 million human beings affected by the disease. More than 80% of persons with epilepsy live in low and middle income countries and most of them in tropical areas. Several emerging, re-emerging and neglected diseases are symptomatic etiologies that jointly contribute to the enormous global burden of epilepsy. Besides the clinical strengths to reduce diagnostic and treatment gaps, other strategies in social, economic, cultural, educational and health policies are needed to prevent and treat appropriately vulnerable and affected persons with epilepsy. From the public health point of view, several of those strategies could be more effective in reducing the incidence and burden of the disease than the clinical approach of diagnosis and treatment. Special attention has to be given to stigma reduction and promotion of human rights. Several aspects mentioned in this abstract slip away the scope of the article, but it is a remainder to approach epilepsy in an inter- and transdisciplinary manner, an integral and pertinent approach needed and requested in tropical counties. The article focuses only on emergent and re-emergent etiologies of epilepsy in the tropics like malaria, HIV, neurocysticercosis, viral encephalitis and traumatic brain injury.